(3JfXje GdOhdI hEOGQI GdEbJUGO Gdbhej (B/s - (3Yajaj, UOjb eMeOs ((3GdbGgQI(B: s (3ecJHI Yjf GdTeS(B, s, 2003)
(3EYGOI UjGZI GdOhdI aj Xd GdJMhdGJ GdEbJUGOjI GdLOjOI, GdeJWGdHGJ GdEOGQjI, eDSSI GdOhdI, GdedGeM GdQFjSjI hGdCTcGd GdJfXjejI aj JfXje GdLgGR GdEOGQj GdMchej, GdJfXje GdQFjSj GdMGdj ddOhdI, eTcdGJ hEJLGgGJ JQTjO GdJfXje GdMchej, GdebheGJ GdCSGSjI ddJMce GdeMdji aj eUQ,ESJQGJjLjI GdJNUUjI dJWhjQ bWGY GdCYeGd GdYGe, fXGe ebJQM dENJjGQ GdbjGOGJ, GdEWGQ GdYGe dESJQGJjLjI GdJfejI GdEOGQjIs
Keywords: (3GdEOGQIs; (3GdEbJUGOs; (3GdOhdIs